Obstructive sleep apnea, the NLRP3 inflammasome and the potential effects of incretin therapies - Wei, Michelle; Teske, Jennifer A.; Mashaqi, Saif; Combs, Daniel (Frontiers in Sleep, 2025)
Obstructive sleep apnea (OSA) is a common sleep disorder associated with serious neurological and cardiovascular complications. Intermittent hypoxia and reoxygenation, a key feature of OSA, produces molecular signals that activate various inflammatory pathways, notably the inflammasome—a multiprotein complex that promotes the release of pro-inflammatory cytokines including IL-18 and IL-1β. This results in systemic inflammation, which contributes to the development of the neurological and cardiovascular complications seen in OSA. In this review, we will first examine the pathways through which intermittent hypoxia induces inflammasome activation. Then, we will connect the inflammasome to the downstream neurological and cardiovascular effects of OSA. Finally, we will explore potential interactions between the inflammasome and OSA treatments including Continuous Positive Airway Pressure therapy and glucagon like peptide-1 receptor agonists (GLP-1RAs).